A novel immunohistochemical protocol for paraffin embedded tissue sections using free-floating techniques - Muniz Partida, Carolina; Walters, Eric (Frontiers in Neuroanatomy, 2023)
Immunohistochemistry (IHC) is a well-established and widely used protocol used to visualize tissue architecture, protein expression and localization. Free-floating methods for IHC employ tissue sections that are cut from a cryostat or vibratome. The limitations of these tissue sections are tissue fragility, poor morphology, and the need to use sections of 20–50 μm. In addition, there is a void of information regarding the use of free floating immunohistochemical techniques on paraffin embedded tissue. To address this, we developed a free-float IHC protocol with paraffin embedded tissue (PFFP) that saves time, resources, and tissues. PFFP localized GFAP, olfactory marker protein, tyrosine hydroxylase, and Nestin expression in mouse hippocampal, olfactory bulb, striatum, and cortical tissue. Successful localization of these antigens was achieved using PFFP with and without antigen retrieval, with subsequent chromogenic DAB (3,3′-diaminobenzidine) development and immunofluorescence detection methods. The application of the PFFP in combination with methodologies of in situ hybridization, protein/protein interactions, laser capture dissection, and pathological diagnosis expands the versatility of paraffin embedded tissues.